GAMBARAN MIKROSKOPIS SEDIAAN HAPUSAN SERVIKS PADA PASIEN GONORRHEA DI PUSKESMAS II DENPASAR SELATAN - Pani Ambarasari, Ni Luh Wayan; Sutirta Yasa, I W P (E-Jurnal Medika Udayana; Vol 6 No 7 (2017): E-Jurnal Medika Udayana, 2017)
Gonorrhea is the second-most sexual transmitted disease after Chlamydia infection in Europe. This infection caused by gram negative bacterial Neisseria Gonorrhoeae which usually infect the columnar epithelium of urethra, endocervix, rectum, pharynx, and conjunctiva. Transmission of the infection through genitalia organ, genitalia-anorectal, oro-genital or oro-anal, or perinatal direct infection from the mother to baby which the mother already infected. Infection in male three times more than female because case in male usually symptomatic than female which usually asymptomatic. Purpose of this research is to know the microscopic picture of gonorrhea infection in female. This microscopic picture can be used as the first diagnose to prevent the spreading N. Gonorrhea infection. This study used cross sectional design. The data was taken from patients' medical records of women with gonorrhea who have cervical smear tests at Puskesmas II Denpasar Selatan. The result of microscopic picture from 24 samples cervical swab, there was finding gram-negative diplococcal. Almost patient was in asymptomatic conditions. About 54.2% are the patients with lower education at least elementary school. Microscopic picture of the patient we can claim all of the cervical swab contain gram-negative diplococcal and 23 samples contain with gram-negative diplococcal intracellular in polymorphonuclear cells. After this study done it can be concluded that we found gram-negative diplococcal intracellular in polymorphonuclear cells from gonorrhea patients’ cervical smears.  Keywords: Gonorrhea, Gram-negative diplococcal, cervix, Polymorphonuclear